Implementasi Kebijakan Pendidikan dalam Membangun Karakter di MAN 1 Deli Serdang - Muhammad Iqbal; Dian Fahmi; Dini Rahmawati Nasution; Nur Halija Dalimunthe (Journal on Education, 2023)
Education Implementation has a goal direction so that the educational policies that have been created are realized. This study of education policy aims to provide a written description of the policy implementation process, including in terms of education and character. The purpose of policy implementation is to set directions so that policy objectives can be realized. This study aims to describe the process of policy implementation including education policy. In implementing it, it is necessary to pay attention to the process, it is necessary to consider the strategies and approaches used, the stages of formulation, the adequacy and completeness of the administration. This is for the realization of success in implementing education policies. In policy implementation, there is a process that must be followed, including certain strategies and approaches that must be taken, as well as several completeness and adequacy that must be met. This is none other than for the sake of realizing success in implementing policies.